Problematika Pendidikan Dalam Menyongsong Masa Depan Yang Gemilang - Nisaul Fatona (ADALAH, 2020)
Abstract: Education is an effort to improve the quality of human life. Every human being needs education, whenever and wherever. Education is a way to educate the nation’s children and welcome a bright future. One of the goals of education is that a person who can compete in the future and be able to develop one’s potential and talent is formed. There are children and the young stopped from school, did not continue their education to the higher grade, therefore their future is dangerous.Keywords: Education, the future, the resounding                                      Abstrak: Pendidikan merupakan suatu upaya untuk meningkatkan kualitas kehidupan manusia. Setiap manusia membutuhkan pendidikan sampai kapanpun dan dimanapun. Pendidikan merupakan jalan untuk mencerdaskan anak bangsa serta menyongsong masa depan gemilang. Salah satu tujuan pendidikan ialah membentuk sosok yang mampu bersaing di masa depan serta mampu mengembangkan potensi dan bakat seseorang. Pada kenyataannya banyak generasi muda yang putus sekolah dan tidak melanjutkan pendidikannya ke jenjang yang lebih tinggi, sehingga masa depan mereka terancam suram.Kalimat kunci: pendidikan, masa depan, gemilang